1983
DOI: 10.1136/pgmj.59.695.560
|View full text |Cite
|
Sign up to set email alerts
|

Fractures of the pelvis

Abstract: Associated injuries were common (2*19 per patient). Some of these lesions were the result of the causative trauma. Some others, however, were related to certain types of pelvic fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…2 Population studies have shown these fractures to have an overall incidence of 37/100 000 patient years 3. The highest frequency is seen in women over the age of 85 years (450/100 000 patient years).…”
mentioning
confidence: 99%
“…2 Population studies have shown these fractures to have an overall incidence of 37/100 000 patient years 3. The highest frequency is seen in women over the age of 85 years (450/100 000 patient years).…”
mentioning
confidence: 99%